The representation of identity on public television, a study of the miniseries ‘Déjala morir’ (Encuentros, 2022)
This paper answer to how meanings, produce by audience and producer of biographic miniseries Déjala morir - which airs on the public television station Telecaribe that tells the story of Juana Emilia Herrera - converge and diverge. To achieve it, four methods were applied to study: a textual analysis of the miniseries, an in-depth interview for its creator, a focus group with the audience and a qualitative content analysis of comments made on Facebook profiles of El Heraldo, and El Espectador when users who watch the series publish their opinions about it. As representative results, three key categories were found: the representation of the Caribbean through the audiovisual, the Caribbean woman, and the critical audience. Finally, it is established that the audience finds a representation of its territory, which the protagonist represents the values and talent of ‘The Emilia Girl’ and, finally, is evidenced by a critical audience that assumes a divergent posture with television productions Commercial and convergent with the content issued in Déjala morir.